Integrated investigation of the genotoxicity of a contaminated estuary sediment extract using LacZ plasmid-based transgenic mice - Pinto, Miguel (2017)
As targets for diverse anthropogenic activities, estuaries are reservoirs for a variety of pollutants. Recent studies showed that sediments from a Portuguese Estuary were cytotoxic and genotoxic in a human liver cell line and in local aquatic species, possibly due to the presence of PAHs and metals. However, the extrapolation of ecological risk to risk to human health is difficult and in vivo studies are crucial to better reflect human exposure and effects. This study aimed at investigating the genotoxic potential of a contaminated sediment sample from a local fishing area of the Estuary, combining the analysis of multiple endpoints in the LacZ plasmid-based transgenic mouse model. Groups of LacZ mice were exposed through drinking water to two dilutions of an estuarine sediment extract from an impacted site, as well as to solvent control, for 28 days. The DNA and chromosome damaging effects were monitored in peripheral blood at 7 day intervals using the Comet (plus DNA repair endonucleases) and Micronucleus (MN) assays in peripheral blood cells. After euthanasia, DNA and oxidative DNA damage were analyzed in several mouse organs, and LacZ mutant frequency was determined in liver. The results showed a time-dependent increase in MN frequency for each treated group. In contrast, no induction of DNA or oxidative DNA damage was observed in any organ, irrespectively of the dose; likewise, no mutation induction was detected in the liver of exposed mice. Overall, the increase in the MN frequency in mice orally exposed to the sediment extract is suggestive of adverse effects on human health, and points to the need of further research in the human population resident in the affected area.